2020
DOI: 10.1097/meg.0000000000001840
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of cytomegalovirus DNA quantitation in gastrointestinal biopsies: comparison with histopathological data and blood cytomegalovirus DNA

Abstract: Objectives This study aims to improve the diagnosis of gastrointestinal (GI) cytomegalovirus (CMV) disease. It presents the results of a novel study in which CMV blood viral load (BVL), tissue viral load (TVL) determined by PCR and hematoxylin-eosin (HE)/immunohistochemistry (IHC) results of GI biopsies are examined comparatively. Methods CMV DNA was investigated by quantitative real-time PCR in blood and GI biopsy specimens of 76 patients suspected of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[21] In a similar study, the blood CMV-DNA PCR results were negative in 33.3% of cases with positive tissue CMV-DNA PCR results. [22] We suggest that all IBD patients who are hospitalized for exacerbations be evaluated using tissue CMV-DNA PCR in colonic biopsy specimens for the diagnosis of CMV colitis. CMV-DNA PCR positivity can be detected in tissue, although CMV-DNA PCR is negative in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] In a similar study, the blood CMV-DNA PCR results were negative in 33.3% of cases with positive tissue CMV-DNA PCR results. [22] We suggest that all IBD patients who are hospitalized for exacerbations be evaluated using tissue CMV-DNA PCR in colonic biopsy specimens for the diagnosis of CMV colitis. CMV-DNA PCR positivity can be detected in tissue, although CMV-DNA PCR is negative in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…[15,26] In the present study, the IHC test was positive in only 5 (21.7%) of the 23 patients positive for CMV-DNA PCR in the colonic mucosa. Alacam et al [22] reported that 35.1% of cases with CMV-DNA PCR-positive tissue were found to be IHC positive. Although IHC is the gold standard, it alone may not be sufficient for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The details on the techniques used for specimens’ analysis were omitted in most studies. hCMV‐specific immunohistochemistry and in situ hybridization procedures are probably more reliable than direct microscopy and hematoxylin‐eosin staining, 108 but the cost‐effectiveness of these methods and the theoretical advantage of combining multiple diagnostic modalities have yet to be assessed 87 …”
Section: Discussionmentioning
confidence: 99%
“…The details on the techniques used for specimens' analysis were omitted in most studies. hCMV-specific immunohistochemistry and in situ hybridization procedures are probably more reliable than direct microscopy and hematoxylin-eosin staining, 108 but the costeffectiveness of these methods and the theoretical advantage of combining multiple diagnostic modalities have yet to be assessed. 87 The first-line treatment in the majority of post-transplant hCMV-GID episodes consisted of intravenous ganciclovir administration, eventually followed by valganciclovir as secondary prophylaxis in some cases.…”
Section: Patientsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Studies included in the present meta-analysis, including quantitative and qualitative assessment. References [ 38 , 48 , 49 , 51 , 52 , 53 , 54 , 55 , 73 , 75 , 93 , 99 , 100 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ,…”
mentioning
confidence: 99%